2013
DOI: 10.11628/ksppe.2013.16.4.199
|View full text |Cite
|
Sign up to set email alerts
|

User Satisfaction and Preference of the Hotel Roof Garden

Abstract: With the city of Seoul undergoing rapid urban development in the last decade, rooftop green projects have been expanding continuously with support that started from the city of Seoul. This research was conducted to analyze the current usage of roof gardens and stimulate development of new roof gardens. From rooftop gardens of three hotels selected in Seoul and Incheon, customer satisfaction and preferences were examined and this research intended to propose renovation plans for roof gardens. From the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The subfactor with the highest positive correlation with frequency of use aside from overall satisfaction was visual satisfaction (r = 0.221), indicating that to increase user frequency of garden use, it is more important to well arrange visually appealing elements compared to other subfactors. This is similar to the study result by Kim et al (2013) reporting that users showed high preference for gardens with a theme space using colorful and decorative theme species in all four seasons. Moreover, Lee and Eom (2019) examined user satisfaction with a university campus cherry blossom tunnel and reported that the image and scenic beauty of the space must be improved to promote user satisfaction.…”
Section: Correlation Between Satisfaction With Garden Use and Garden ...supporting
confidence: 91%
See 1 more Smart Citation
“…The subfactor with the highest positive correlation with frequency of use aside from overall satisfaction was visual satisfaction (r = 0.221), indicating that to increase user frequency of garden use, it is more important to well arrange visually appealing elements compared to other subfactors. This is similar to the study result by Kim et al (2013) reporting that users showed high preference for gardens with a theme space using colorful and decorative theme species in all four seasons. Moreover, Lee and Eom (2019) examined user satisfaction with a university campus cherry blossom tunnel and reported that the image and scenic beauty of the space must be improved to promote user satisfaction.…”
Section: Correlation Between Satisfaction With Garden Use and Garden ...supporting
confidence: 91%
“…Purposes and frequency of campus garden use by university studentsKim et al (2013) that factors such as cultural experience and exercise focused on rest areas affect user preference for hotel rooftop gardens.…”
mentioning
confidence: 99%
“…The research analyzed and reclassified the surveyed items of the advanced researches on the analysis of preference for garden design or the analysis of satisfaction for the garden elements (Ahn, 2004;Jung, 2004;Lee and Kim, 2007;Park et al, 2008;Hong, 2011;Jeon et al, 2011;Kim, 2012;Kim et al, 2012;Kim et al, 2013;Shin et al, 2011) to figure out the garden elements of community resting areas and designed the on-site survey form. The surveyed items of the advanced researches are divided into outdoor and indoor garden types, including accessibility, motivation of visit, facility, plant management, function and environment and resting area.…”
Section: Design Of Survey Formmentioning
confidence: 99%